Additional data on morphology of Actinella leontopithecus-rosalia Costa (Bacillariophyta, Eunotiaceae) - Tremarin, Priscila I.; Kim, Kwang I.m.b.; Marra, Raquel C.; Ludwig, Thelma A.v. (Phytotaxa, 2016)
Actinella leontopithecus-rosalia is a poorly known diatom described from southeast Brazil. Its similarity with other Actinella taxa and the lack of morphological data make it difficult the species recognition by researchers. This study addresses unpublished morphologic and morphometric details of frustule and expands the geographic distribution of A. leontopithecus-rosalia to tropical and subtropical regions of South America. The analysis of type and paratype materials and additional Brazilian samples under light and electron microscopy allowed us to establish the synonymy of A. lange-bertalotii with A. leontopithecus-rosalia, and to compare them also with the related A. modesta.